Hemolytic anemia in two patients with glioblastoma multiforme: A possible interaction between vorinostat and dapsone. (June 2015) - Lewis, Jennifer A; Petty, William J; Harmon, Michele; Peacock, James E; Valente, Kari; Owen, John; Pirmohamed, Munir; Lesser, Glenn J
Patients undergoing treatment for glioblastoma multiforme are routinely placed on prophylactic treatment for Pneumocystis jirovecii pneumonia because of significant therapy-induced lymphopenia. In patients with sulfa allergies, dapsone prophylaxis is often used due to its efficacy, long half-life, cost effectiveness, and general safety at low doses. However, dapsone may uncommonly induce a hemolytic anemia, particularly in patients deficient of glucose-6-phosphate dehydrogenase. This hemolysis is thought to be a result of oxidative stress on red blood cells induced by dapsone metabolites which produce reactive oxygen species that disrupt the red blood cell membrane and promote splenic sequestration. A single case report of dapsone-induced hemolytic anemia in a patient with glioblastoma multiforme has been reported. We present two patients with glioblastoma multiforme who developed severe hemolytic anemia shortly after initiating therapy with vorinostat, a pan-active histone deacetylase inhibitor, while on prophylactic dapsone. There are several potential mechanisms by which histone deacetylase inhibition may alter dapsone metabolism including changes in hepatic acetylation or N -glucuronidation leading to an increase in the bioavailability of dapsone's hematotoxic metabolites. In addition, vorinostat may lead to increased hemolysis through inhibition of heat shock protein-90, a chaperone protein that maintains the integrity of the red blood cell membrane cytoskeleton. The potential interaction between dapsone and vorinostat may have important clinical implications as more than 10 clinical trials evaluating drug combinations with vorinostat in patients with malignant glioma are either ongoing or planned in North America.